Changes in the retina and choroid in patients with internal carotid artery stenosis: a systematic review and meta-analysis - Hou, Xiaoyu; Jie, Chuanhong; Liu, Ziqiang; Bi, Xuqi; Deng, Yu; Li, Yuanyuan; Wang, Jingying; Zhang, Weiqiong (Frontiers in Neuroscience, 2024)
Background Internal carotid artery stenosis (ICAS) is a prevalent vascular condition associated with ischemic cerebrovascular disease. The ophthalmic artery is the first branch of the internal carotid artery stenosis (ICA). Given the crucial role of the ICA in ocular perfusion, we aimed to assess the thickness and vessel density of the retina and choroid in individuals with ICAS. Methods The PubMed and Embase databases were searched from inception to 10 January 2023 for studies evaluating retinal and choroidal changes between ICAS patients and healthy controls using optical coherence tomography (OCT) or optical coherence tomography angiography (OCTA). Data of interest were extracted and analyzed using Stata software version 16. Results Thirteen studies involving 419 ICAS eyes and 398 healthy eyes were included. The pooled results demonstrated that the average thickness of peripapillary retinal nerve fiber layer (pRNFL) (WMD = −0.26, 95% CI: −0.45 to −0.08, P = 0.005), ganglion cell complex (GCC) (WMD = −0.36, 95% CI: −0.65 to −0.06, P = 0.017), and choroid (WMD = −1.06, 95% CI: −1.59 to −0.52, P = 0.000), were significantly thinner in patients with ICAS than in healthy controls. The overall vessel density of the radial peripapillary capillaries (RPC) in whole-image scans was lower in ICAS patients than in healthy control subjects (WMD = −0.94, 95% CI: −1.49 to −0.39, P = 0.001). No differences were detected in the vessel density of the superficial capillary plexus (SCP) (WMD = −0.84, 95% CI: −1.15 to −0.53, P = 0.092), the deep capillary plexus (DCP) (WMD = −0.27, 95% CI: −0.56 to 0.03, P = 0.074), or the choriocapillaris (CC) (WMD = −0.39, 95% CI: −1.12 to 0.35, P = 0.300). Conclusion This systematic review and meta-analysis demonstrated that ICAS can reduce the vessel density of the RPC and the thickness of the retina and choroid. The retinal and choroidal microvasculature is a potential biomarker of the initial signal of ICAS. Systematic review registration https://inplasy.com/, identifier NPLASY202410038